Bhamati and Vivaraṇa schools of Advaita Vedanta : a critical approach - Roodurmum, Pulasth Soobah; Kanshi Ram; Vacaspati Miśra; Prakaśatman Muni (Delhi : Motilal Banarsidass Publishers, 2002)
Study of Bhāmatī of Vācaspatimiśra, fl. 976-1000 and Pañcapadikāvivaraṇa of Prakāśātman, classical work on Advaita and Vedanta philosophy.
Bibliografija: str. [273]-280 i kazalo
Includes passages in Sanskrit.
Keywords: indijska filozofija -- Advaita Vedanta -- škola Bhamati -- škola Vivarana